Benzenesulfonic acid-ammonium hydrogen bond organic framework material as well as preparation method and application thereof
By using hydrogen bond organic frame material with a three-dimensional hydrogen bond network structure formed by sulfonic acid groups and ammonium ions in the proton exchange membrane fuel cell, the problem of insufficient stability and conductivity of the proton exchange membrane under high temperature and high humidity conditions in the prior art is solved, and efficient proton conduction performance is achieved.
Patent Information
- Application Number
- CN202411883090.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-19
AI Technical Summary
In existing proton exchange membrane fuel cells, the commercial perfluorosulfonic acid Nafion membrane has problems such as excessive expansion, limited operating temperature range and low fuel permeability under high temperature and high humidity conditions, which hinders its large-scale promotion and application.
The hydrogen bond organic framework material, including 1,5-NDS_NH4, BPDS_NH4 and MTBS_NH4 materials, was prepared by gas phase diffusion crystallization and evaporation crystallization.
The thermal stability and conductivity of hydrogen bonded organic frame materials are significantly improved, and the conductivity reaches up to 2.1×10-1S/cm under high temperature and high humidity conditions, and is suitable for efficient proton exchange membrane fuel cells.
Smart Images

Figure HDA0005198652330000011 
Figure HDA0005198652330000012 
Figure HDA0005198652330000013
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen-bonded organic framework materials, and in particular relates to hydrogen-bonded organic framework materials and preparation methods and applications thereof. Background Art
[0002] In order to cope with the two major environmental crises of energy depletion and global warming, the development of efficient and clean energy has become a top priority. Proton exchange membrane fuel cells (PEMFC) have attracted widespread attention due to their advantages of low emissions and high power density. Proton exchange membrane is an important component of PEMFC. The currently commercially available perfluorosulfonic acid Nafion membrane exhibits excellent proton conductivity under conditions below 85°C and high humidity, but its excessive expansion, limited operating temperature range and low fuel permeability have hindered its large-scale promotion and application. In order to further improve the performance of PEMFC, it is urgent to develop proton conductive materials with high proton conductivity and high robustness.
[0003] Hydrogen-bonded organic frameworks (HOFs) are a new type of functional crystalline materials that have attracted increasing attention in the field of proton conduction because they are self-assembled through weak non-covalent interactions, namely hydrogen bonds. These organic building blocks can accommodate protic solvent molecules (such as H 2 O、NH 3 In these networks, proton donor and acceptor functional groups together form an efficient proton transport path. Therefore, hydrogen-bonded organic framework materials have become a potential candidate platform for solid-state proton conductive materials due to their high proton conductivity, solution processability, reusability, and ease of large-scale synthesis from cheap raw materials, showing broad application prospects in fuel cell technology. However, as hydrogen bonds are weak interaction forces, hydrogen-bonded organic framework materials driven by them have poor stability, and the electrical conductivity of hydrogen-bonded organic framework materials still needs to be improved. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the prior art to a certain extent. To this end, the present invention provides a hydrogen-bonded organic framework material and a preparation method thereof, wherein the hydrogen-bonded organic framework material has excellent thermal stability and electrical conductivity.
[0005] Therefore, in the first aspect of the present invention, the present invention proposes a hydrogen-bonded organic framework material, wherein the structural units of the hydrogen-bonded organic framework material include sulfonic acid groups and ammonium ions, and the sulfonic acid groups and the ammonium ions are connected by charge-assisted hydrogen bonds to form a three-dimensional hydrogen-bonded network structure; the hydrogen-bonded organic framework material includes 1,5-NDS_NH 4 Materials, BPDS_NH 4 Materials, MTBS_NH 4At least one of the materials; 1,5-NDS_NH 4 The chemical formula of the material is [(C 10 H 8 O 6 S 2 )(NH 4 ) 2 ]n, BPDS_NH 4 The chemical formula of the material is [(C 12 H 8 O 6 S 2 )(NH 4 ) 2 ]n,MTBS_NH 4 The chemical formula of the material is [(C 25 H 16 O 12 S 4 )(NH 4 ) 4 ]n, where n is a positive integer.
[0006] In the hydrogen-bonded organic framework material of the present invention, the sulfonic acid groups and the ammonium ions are connected to form a three-dimensional supramolecular structure through charge-assisted hydrogen bonds, forming a continuous hydrogen bond chain, thereby effectively improving the thermal stability and electrical conductivity of the material.
[0007] In some embodiments, 1,5-NDS-NH 4 The material meets at least one of the following requirements:
[0008] (1) 1,5-NDS_NH 4 The structural unit of the material belongs to the monoclinic system, the space group is P21 / c, and the molecular formula is C 10 H 16 N 2 O 6 S 2 , unit cell parameters: α=γ=90°, β=103.4°;
[0009] (2) 1,5-NDS_NH 4 The material is polymerized by multiple repeating units, each of which contains one 1,5-NDS molecule and two ammonium ions, and 1,5-NDS is 1,5-naphthalene disulfonic acid; the sulfonic acid groups on the 1,5-NDS molecules and the ammonium ions are repeatedly polymerized to form a three-dimensional hydrogen bond network;
[0010] (3)1,5-NDS_NH 4 The thermal stability temperature of the material reaches 320℃;
[0011] (4) 1,5-NDS_NH 4The conductivity of the material at 50-95% RH and 45-90°C is 5.6×10 -6 ~6.6×10 -2 S / cm; RH is relative humidity.
[0012] In some embodiments, BPDS_NH 4 The material meets at least one of the following requirements:
[0013] (a)BPDS_NH 4 The structural unit of the material belongs to the monoclinic system, the space group is P21 / c, and the molecular formula is C 12 H 16 N 2 O 6 S 2 , unit cell parameters: α=γ=90°, β=96.7°;
[0014] (b)BPDS_NH 4 The material is polymerized by multiple repeating units, each of which contains one BPDS molecule and two ammonium ions, and BPDS is 4,4'-biphenyl disulfonic acid; the sulfonic acid groups on the BPDS molecules and the ammonium ions are repeatedly polymerized to form a three-dimensional hydrogen bond network; the three-dimensional hydrogen bond network has closed channels and a porosity of 11%;
[0015] (c)BPDS_NH 4 The thermal stability temperature of the material reaches 200°C;
[0016] (d)BPDS_NH 4 The conductivity of the material at 50-95% RH and 45-90°C is 1.7×10 -5 ~2.1×10 -1 S / cm; RH is relative humidity.
[0017] In some embodiments, MTBS_NH 4 The material meets at least one of the following requirements:
[0018] (A)MTBS_NH 4 The structural unit of the material belongs to the orthorhombic system, the space group is I4, and the molecular formula is C 25 H 32 N 4 O 12 S 4 , unit cell parameters: α=β=γ=90°;
[0019] (B)MTBS_NH 4The material is polymerized by multiple repeating units, each of which contains one MTBS and four ammonium ions, and MTBS is tetrakis(4-sulfonatophenyl)methane; the sulfonic acid groups on the MTBS molecules repeatedly polymerize with the ammonium ions to form a three-dimensional hydrogen bond network;
[0020] (C)MTBS_NH 4 The thermal stability temperature of the material reaches 160°C;
[0021] (D)MTBS_NH 4 The conductivity of the material at 50-95% RH and 45-90°C is 2.3×10 -6 ~4.6×10 -2 S / cm; RH is relative humidity.
[0022] In a second aspect of the present invention, the present invention provides a method for preparing a hydrogen-bonded organic framework material, comprising the following steps:
[0023] The sulfonic acid ligand, the solvent and the ammonium source solution are mixed to carry out a polymerization reaction to obtain a mixed solution;
[0024] The mixed solution is subjected to crystallization treatment to obtain flaky crystals;
[0025] The supernatant is removed, and the flaky crystals are naturally dried to obtain a hydrogen-bonded organic framework material.
[0026] The invention obtains hydrogen bond organic framework material by adopting a crystallization treatment method, and has simple preparation process, convenient operation and high yield.
[0027] In some embodiments, the crystallization method includes at least one of evaporation crystallization and vapor diffusion crystallization.
[0028] In some embodiments, the vapor diffusion crystallization method includes a poor solvent, and the poor solvent includes at least one of ethyl acetate and acetone.
[0029] In some embodiments, 1,5-NDS-NH 4 The materials include at least one of the following:
[0030] (i) Sulfonic acid ligands include 1,5-NDS;
[0031] (ii) the solvent includes N,N-dimethylformamide;
[0032] (iii) the ammonium source solution comprises an ammonium chloride solution having a molar concentration of 1 mol / L;
[0033] (iv) the molar ratio of 1,5-NDS to ammonium chloride solution is 1:(2-4);
[0034] (v) the ratio of 1,5-NDS to solvent is 8 to 15 mg / mL;
[0035] (vi) The crystallization method includes vapor diffusion crystallization.
[0036] In some embodiments, BPDS-NH 4 The materials include at least one of the following:
[0037] (I) Sulfonic acid ligands include BPDS;
[0038] (II) the solvent includes methanol;
[0039] (III) the ammonium source solution comprises an ammonium chloride solution having a molar concentration of 1 mol / L;
[0040] (IV) the molar ratio of BPDS to ammonium chloride solution is 1:(2-4);
[0041] (V) The ratio of BPDS to solvent is 8-12 mg / mL.
[0042] In some embodiments, MTBS-NH 4 The materials include at least one of the following:
[0043] (1) Sulfonic acid ligands include MTBS;
[0044] (2) The solvent includes methanol;
[0045] (3) the ammonium source solution includes an ammonium chloride solution having a molar concentration of 1 mol / L;
[0046] (4) The molar ratio of MTBS to ammonium chloride solution is 1:(4-6);
[0047] (5) The ratio of MTBS to solvent is 10-12 mg / mL;
[0048] (6) The crystallization treatment method includes a vapor diffusion crystallization method.
[0049] In the third aspect of the present invention, the present invention provides a proton exchange, including the hydrogen-bonded organic framework material of the first aspect, or, including the hydrogen-bonded organic framework material obtained by the preparation method of the second aspect.
[0050] Therefore, the proton exchange membrane of the present invention has excellent thermal stability and proton conductivity.
[0051] In a fourth aspect of the present invention, the present invention provides a proton exchange membrane fuel cell, comprising the proton exchange membrane of the third aspect.
[0052] Therefore, the proton exchange membrane fuel cell of the present invention has excellent thermal stability and proton conductivity.
[0053] Compared with the prior art, the present invention has the following beneficial technical effects:
[0054] (1) The structural unit of the hydrogen-bonded organic framework material of the present invention includes a sulfonic acid group and an ammonium ion. The four hydrogen atoms on the ammonium ion can be used to form hydrogen bonds, thereby increasing the number of hydrogen bonds and improving the stability of the hydrogen-bonded network structure. At the same time, the proton conductivity of the hydrogen-bonded organic framework material is effectively improved, and the conductivity can reach up to 2.1×10 -1 S / cm.
[0055] (2) The hydrogen-bonded organic framework material of the present invention can be obtained by gas phase diffusion crystallization and evaporation crystallization, and its preparation process is simple, easy to operate, and has a high yield.
[0056] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0058] Figure 1 1,5-NDS_NH prepared in Example 1 4 Schematic diagram of the crystal structure of hydrogen-bonded organic framework materials;
[0059] Figure 2 BPDS_NH prepared in Example 2 and Example 3 4 Schematic diagram of the crystal structure of hydrogen-bonded organic framework materials;
[0060] Figure 3 MTBS_NH prepared in Example 4 4 Schematic diagram of the crystal structure of hydrogen-bonded organic framework materials;
[0061] Figure 4 The XRD comparison patterns of the hydrogen-bonded organic framework material crystal powder prepared in Example 1 (A), Example 2 (B) and Example 4 (C) and the simulated single crystal structure thereof;
[0062] Figure 5 It is a thermogravimetric analysis comparison diagram of the hydrogen-bonded organic framework material crystal powder prepared in Example 1 (A), Example 2 (B) and Example 4 (C) and its original benzenesulfonic acid ligand;
[0063] Figure 6It is the Nengquist curve diagram obtained in Example 5 for the hydrogen-bonded organic framework material crystal powder prepared in Example 1 (A), Example 2 (B) and Example 4 (C). DETAILED DESCRIPTION
[0064] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0065] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0066] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0067] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.
[0068] In a first aspect of an embodiment of the present invention, the present invention proposes a hydrogen-bonded organic framework material, wherein the structural unit of the hydrogen-bonded organic framework material comprises a sulfonic acid group and an ammonium ion, wherein the sulfonic acid group and the ammonium ion are connected by charge-assisted hydrogen bonds to form a three-dimensional hydrogen-bonded network structure; the hydrogen-bonded organic framework material comprises 1,5-NDS_NH 4 Materials, BPDS_NH 4 Materials, MTBS_NH 4 At least one of the materials; 1,5-NDS_NH 4 The chemical formula of the material is [(C 10 H 8 O 6 S 2 )(NH 4 ) 2 ]n, BPDS_NH 4 The chemical formula of the material is [(C 12 H 8 O 6 S 2 )(NH 4 ) 2]n,MTBS_NH 4 The chemical formula of the material is [(C 25 H 16 O 12 S 4 )(NH 4 ) 4 ]n, where n is a positive integer.
[0069] According to an embodiment of the present invention, in the hydrogen-bonded organic framework material of the present invention, the sulfonic acid group and the ammonium ion are connected into a three-dimensional supramolecular structure by charge-assisted hydrogen bonds to form a continuous hydrogen-bonded chain. The hydrogen-bonded organic framework material of the prior art usually uses organic ligands to connect with each other to build hydrogen-bonded motifs. Compared with the hydrogen-bonded organic framework material of the present invention, the present invention introduces the inorganic molecule of ammonium ion, which is not only much smaller than the organic building unit in size, but also makes the connection and regulation of hydrogen bonds more flexible and changeable, and the four hydrogen atoms on the ammonium ion can be used to form hydrogen bonds, thereby increasing the number of hydrogen bonds and improving the stability of the hydrogen-bonded network structure. The present invention uses three different sulfonic acid ligands and ammonium ions to prepare three kinds of hydrogen-bonded organic framework materials under different synthesis conditions, which also reflects the universality of ammonium ions as nodes for regulating hydrogen-bonded network structures to connect sulfonic acid ligands. After the organic ligand forms a hydrogen-bonded network structure, its thermal stability is significantly improved. In addition, the anionic sulfonic acid group and the cationic ammonium ion can act as proton carriers to transport protons, effectively improving the proton conductivity of the hydrogen-bonded organic framework material. The conductivity can reach up to 2.1×10 -1 S / cm. This indicates that the hydrogen-bonded organic framework material of the present invention has excellent thermal stability and electrical conductivity.
[0070] In some embodiments of the present invention, 1,5-NDS-NH 4 The material meets at least one of the following requirements:
[0071] (1) 1,5-NDS_NH 4 The structural unit of the material belongs to the monoclinic system, the space group is P21 / c, and the molecular formula is C 10 H 16 N 2 O 6 S 2 , unit cell parameters: α=γ=90°, β=103.4°;
[0072] (2) 1,5-NDS_NH 4 The material is polymerized by multiple repeating units, each of which contains one 1,5-NDS molecule and two ammonium ions, and 1,5-NDS is 1,5-naphthalene disulfonic acid; the sulfonic acid groups on the 1,5-NDS molecules and the ammonium ions are repeatedly polymerized to form a three-dimensional hydrogen bond network;
[0073] (3)1,5-NDS_NH 4 The thermal stability temperature of the material reaches 320℃;
[0074] (4) 1,5-NDS_NH 4 The conductivity of the material at 50-95% RH and 45-90°C is 5.6×10 -6 ~6.6×10 -2 S / cm; RH is relative humidity.
[0075] Therefore, the hydrogen-bonded organic framework material of the present invention has excellent thermal stability and electrical conductivity.
[0076] In some embodiments of the present invention, BPDS_NH 4 The material meets at least one of the following requirements:
[0077] (a)BPDS_NH 4 The structural unit of the material belongs to the monoclinic system, the space group is P21 / c, and the molecular formula is C 12 H 16 N 2 O 6 S 2 , unit cell parameters: α=γ=90°, β=96.7°;
[0078] (b)BPDS_NH 4 The material is polymerized by multiple repeating units, each of which contains one BPDS molecule and two ammonium ions, and BPDS is 4,4'-biphenyl disulfonic acid; the sulfonic acid groups on the BPDS molecules and the ammonium ions are repeatedly polymerized to form a three-dimensional hydrogen bond network; the three-dimensional hydrogen bond network has closed channels and a porosity of 11%;
[0079] (c)BPDS_NH 4 The thermal stability temperature of the material reaches 200°C;
[0080] (d)BPDS_NH 4 The conductivity of the material at 50-95% RH and 45-90°C is 1.7×10 -5 ~2.1×10 -1 S / cm; RH is relative humidity.
[0081] Therefore, the hydrogen-bonded organic framework material of the present invention has excellent thermal stability and electrical conductivity.
[0082] In some embodiments of the present invention, MTBS_NH 4 The material meets at least one of the following requirements:
[0083] (A)MTBS_NH 4 The structural unit of the material belongs to the orthorhombic system, the space group is I4, and the molecular formula is C 25 H 32 N 4 O 12 S 4 , unit cell parameters: α=β=γ=90°;
[0084] (B)MTBS_NH 4 The material is polymerized by multiple repeating units, each of which contains one MTBS and four ammonium ions, and MTBS is tetrakis(4-sulfonatophenyl)methane; the sulfonic acid groups on the MTBS molecules repeatedly polymerize with the ammonium ions to form a three-dimensional hydrogen bond network;
[0085] (C)MTBS_NH 4 The thermal stability temperature of the material reaches 160°C;
[0086] (D)MTBS_NH 4 The conductivity of the material at 50-95% RH and 45-90°C is 2.3×10 -6 ~4.6×10 -2 S / cm; RH is relative humidity.
[0087] Therefore, the hydrogen-bonded organic framework material of the present invention has excellent thermal stability and electrical conductivity.
[0088] In a second aspect of the embodiment of the present invention, the present invention provides a method for preparing a hydrogen-bonded organic framework material, comprising the following steps:
[0089] The sulfonic acid ligand, the solvent and the ammonium source solution are mixed to carry out a polymerization reaction to obtain a mixed solution;
[0090] The mixed solution is subjected to crystallization treatment to obtain flaky crystals;
[0091] The supernatant is removed, and the flaky crystals are naturally dried to obtain a hydrogen-bonded organic framework material.
[0092] According to the embodiment of the present invention, the hydrogen-bonded organic framework material is obtained by a crystallization treatment method, and the preparation process is simple, the operation is convenient, and the yield is high.
[0093] In some embodiments of the present invention, the crystallization method includes at least one of evaporation crystallization and vapor diffusion crystallization.
[0094] In some embodiments of the present invention, the vapor diffusion crystallization method includes a poor solvent, and the poor solvent includes at least one of ethyl acetate and acetone.
[0095] According to an embodiment of the present invention, the poor solvent enters the solute solution in the (good) solvent through gas phase diffusion, so that the solubility of the solute is reduced. When the solubility of the solute is reduced to below the saturation point, the solute begins to crystallize, thereby obtaining flaky crystals. Thus, a hydrogen-bonded organic framework material can be obtained.
[0096] In some embodiments of the present invention, 1,5-NDS-NH 4 The materials include at least one of the following:
[0097] (i) Sulfonic acid ligands include 1,5-NDS;
[0098] (ii) the solvent includes N,N-dimethylformamide;
[0099] (iii) the ammonium source solution comprises an ammonium chloride solution having a molar concentration of 1 mol / L;
[0100] (iv) the molar ratio of 1,5-NDS to ammonium chloride solution is 1:(2-4);
[0101] (v) the ratio of 1,5-NDS to solvent is 8 to 15 mg / mL;
[0102] (vi) The crystallization method includes vapor diffusion crystallization.
[0103] Thus, the 1,5-NDS_NH prepared by the present invention 4 The material has excellent thermal stability and electrical conductivity.
[0104] In some embodiments of the present invention, BPDS-NH 4 The materials include at least one of the following:
[0105] (I) Sulfonic acid ligands include BPDS;
[0106] (II) the solvent includes methanol;
[0107] (III) the ammonium source solution comprises an ammonium chloride solution having a molar concentration of 1 mol / L;
[0108] (IV) the molar ratio of BPDS to ammonium chloride solution is 1:(2-4);
[0109] (V) The ratio of BPDS to solvent is 8-12 mg / mL.
[0110] Thus, the BPDS_NH prepared by the present invention 4 The material has excellent thermal stability and electrical conductivity.
[0111] In some embodiments of the present invention, MTBS-NH 4 The materials include at least one of the following:
[0112] (1) Sulfonic acid ligands include MTBS;
[0113] (2) The solvent includes methanol;
[0114] (3) the ammonium source solution includes an ammonium chloride solution having a molar concentration of 1 mol / L;
[0115] (4) The molar ratio of MTBS to ammonium chloride solution is 1:(4-6);
[0116] (5) The ratio of MTBS to solvent is 10-12 mg / mL;
[0117] (6) The crystallization treatment method includes a vapor diffusion crystallization method.
[0118] Thus, the MTBS_NH prepared by the present invention 4 The material has excellent thermal stability and electrical conductivity.
[0119] In a third aspect of the embodiments of the present invention, the present invention provides a proton exchange membrane, comprising the hydrogen-bonded organic framework material of the first aspect, or the hydrogen-bonded organic framework material obtained by the preparation method of the second aspect.
[0120] Therefore, the proton exchange membrane of the present invention has excellent thermal stability and proton conductivity.
[0121] In a third aspect of the embodiments of the present invention, the present invention provides a proton exchange membrane fuel cell, comprising the proton exchange membrane of the third aspect.
[0122] Therefore, the proton exchange membrane fuel cell of the present invention has excellent thermal stability and proton conductivity.
[0123] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0124] Example 1: Preparation of 1,5-NDS_NH by vapor diffusion crystallization 4 Hydrogen bonded organic framework materials
[0125] (1) Weigh 50 mg of 1,5-NDS and dissolve it in 5 mL of N,N-dimethylformamide solution. Then add 100 μL of 1 mol / L ammonium chloride solution to the solution. After ultrasonic dissolution, filter it using a 0.45 μm nylon filter to obtain a mixed solution.
[0126] (2) The mixed solution was placed in a 10 mL sample bottle, and the open sample bottle was placed in a 50 mL wide-mouth bottle with a cover containing 10 mL of ethyl acetate. The bottle cap was tightened and placed at room temperature. After reacting for 4 days, colorless and transparent flaky crystals were obtained;
[0127] (3) Remove the supernatant and dry the flaky crystals naturally to obtain 1,5-NDS_NH 4 Hydrogen-bonded organic framework materials.
[0128] After determination, 1,5-NDS_NH 4 The yield of hydrogen-bonded organic framework material is 58% (calculated based on the mass of 1,5-NDS). Its structure and unit cell parameters were determined by single crystal X-ray diffractometer. α=γ=90°, β=103.4°, Figure 1 1,5-NDS_NH 4 Schematic diagram of the crystal structure of hydrogen-bonded organic framework materials.
[0129] like Figure 1 As shown, 1,5-NDS_NH 4 The ammonium ion forms a NH…O hydrogen bond with the oxygen atom on the sulfonic acid group, and this is repeated to form a continuous hydrogen bond chain. 4 The asymmetric unit of the material consists of a deprotonated 1,5-NDS and two ammonium ions (NH 4 + ) composition. Protonated NH 4 + The deprotonated sulfonate groups are combined together through charge-assisted hydrogen bonds, which can improve the stability of the hydrogen-bonded organic framework. At the same time, the π-π stacking interaction force between layers also improves the stability of the hydrogen-bonded organic framework.
[0130] Example 2: Preparation of BPDS_NH by evaporation crystallization 4 Hydrogen bonded organic framework materials
[0131] (1) Weigh 50 mg of BPDS and dissolve it in 5 mL of methanol solution. Then add 100 μL of 1 mol / L ammonium chloride solution to the solution. After ultrasonic dissolution, filter it using a 0.45 μm nylon filter to obtain a mixed solution.
[0132] (2) The mixed solution was placed in a 10 mL sample bottle, and the sample bottle was left open at room temperature to slowly evaporate. After 4 days of reaction, colorless and transparent flaky crystals were obtained.
[0133] (3) Remove the supernatant and dry the flaky crystals naturally to obtain BPDS_NH 4 Hydrogen-bonded organic framework materials.
[0134] After determination, BPDS_NH 4 The yield of hydrogen-bonded organic framework material is 54.5% (calculated based on the mass of BPDS). Its structure and unit cell parameters were determined by single crystal X-ray diffractometer. α=γ=90°, β=96.7°, Figure 2 BPDS_NH 4 Schematic diagram of the crystal structure of hydrogen-bonded organic framework materials.
[0135] Example 3: Preparation of BPDS_NH by Vapor Diffusion Crystallization 4 Hydrogen bonded organic framework materials
[0136] (1) Weigh 50 mg of BPDS and dissolve it in 5 mL of methanol solution. Then add 100 μL of 1 mol / L ammonium chloride solution to the solution. After ultrasonic dissolution, filter it using a 0.45 μm nylon filter to obtain a mixed solution.
[0137] (2) The mixed solution was placed in a 10 mL sample bottle, and the open sample bottle was placed in a 50 mL wide-mouth bottle with a cover containing 10 mL of acetone, the bottle cap was tightened, and the bottle was placed at room temperature. After reacting for 7 days, colorless and transparent flaky crystals were obtained;
[0138] (3) Remove the supernatant and dry the flaky crystals naturally to obtain BPDS_NH 4 Hydrogen-bonded organic framework materials.
[0139] After determination, BPDS_NH 4 The yield of hydrogen bonded organic framework material is 35.8% (calculated based on the mass of BPDS). Its structure and unit cell parameters were determined by single crystal X-ray diffractometer. α=γ=90°, β=96.7°, Figure 2 BPDS_NH 4 Schematic diagram of the crystal structure of hydrogen-bonded organic framework materials.
[0140] like Figure 2 As shown, BPDS_NH 4 The ammonium ion forms a hydrogen bond of NH…O with the oxygen atom on the sulfonic acid group, and this is repeated to form a continuous hydrogen bond chain. 4 The asymmetric unit consists of a deprotonated BPDS and two ammonium ions (NH 4 + ) composition. Protonated NH 4 +The deprotonated sulfonic acid groups are bonded together through charge-assisted hydrogen bonds, which helps to enhance the stability of the hydrogen-bonded organic framework. The BPDS molecules between layers are arranged in different orientations, forming a closed pore structure with a porosity of 11%.
[0141] Example 4: Preparation of MTBS_NH by Vapor Diffusion Crystallization 4 Hydrogen bonded organic framework materials
[0142] (1) Weigh 50 mg of MTBS and dissolve it in 5 mL of methanol solution. Then add 100 μL of 1 mol / L ammonium chloride solution to the solution. After ultrasonic dissolution, filter it using a 0.45 μm nylon filter to obtain a mixed solution.
[0143] (2) The mixed solution was placed in a 10 mL sample bottle, and the open sample bottle was placed in a 50 mL wide-mouth bottle with a cover containing 10 mL of ethyl acetate. The bottle cap was tightened and placed at room temperature. After reacting for 4 days, colorless and transparent flaky crystals were obtained;
[0144] (3) Remove the supernatant and dry the flaky crystals naturally to obtain MTBS_NH 4 Hydrogen-bonded organic framework materials.
[0145] After determination, MTBS_NH 4 The yield of hydrogen-bonded organic framework material is 38% (calculated based on the mass of MTBS). Its structure and unit cell parameters were determined by single crystal X-ray diffractometer. α=β=γ=90°, Figure 3 MTBS_NH 4 Schematic diagram of the crystal structure of hydrogen-bonded organic framework materials.
[0146] like Figure 3 As shown, MTBS_NH 4 The ammonium ion forms a hydrogen bond of NH…O with the oxygen atom on the sulfonic acid group, and this is repeated to form a continuous hydrogen bond chain. 4 The asymmetric unit consists of a deprotonated MTBS and four ammonium ions (NH 4 + ) composition. Protonated NH 4 + The deprotonated sulfonate groups are combined together through charge-assisted hydrogen bonds, which can improve the stability of the hydrogen-bonded organic framework. At the same time, the π-π stacking interaction force between layers also improves the stability of the hydrogen-bonded organic framework.
[0147] like Figure 4 As shown, the prepared 1,5-NDS_NH 4 BPDS_NH 4and MTBS_NH 4 Comparison of the X-ray diffraction data simulated by the powder samples of the three materials and the single crystal data shows that the three hydrogen-bonded organic framework materials obtained are consistent with the diffraction data peaks obtained by the simulation, indicating that the hydrogen-bonded organic framework material obtained by the preparation method of the present invention has a high purity and still maintains a stable crystal structure after drying.
[0148] like Figure 5 As shown, the prepared 1,5-NDS_NH 4 , BPDS_NH 4 and MTBS_NH 4 The comparison of the thermogravimetric analysis curves of the three materials with those of the organic ligands (1,5-NDS, BPDS and MTBS) shows that the formation of hydrogen bonds effectively improves the thermal stability of the materials. The thermogravimetric analysis curves of the original ligands all show obvious weight loss at 100°C, but after forming a hydrogen bond network with ammonium ions, 1,5-NDS_NH 4 The weight loss of BPDS_NH 4 The weight loss occurs at 200℃, MTBS_NH 4 Weight loss occurred at 160°C.
[0149] Example 5: Proton conduction performance test of three hydrogen-bonded organic framework materials
[0150] (1) The hydrogen-bonded organic framework materials obtained in Example 1, Example 2 and Example 4 were ground into powders, 90 mg of the powder samples were loaded into 8 mm tablet pressing molds, and after applying a pressure of 7 MPa through a tablet press, the samples pressed into sheets were removed from the molds. The thickness of each sample was 0.18 mm and the area was 0.5024 cm 2 .
[0151] (2) Place the sheet sample into the mold, fix the sample with the metal bars at both ends of the mold, and place the mold into a constant temperature and humidity chamber and connect it to the electrochemical workstation. Use the constant temperature and humidity chamber to adjust the temperature and humidity, control the relative humidity to be stable at 95%, and adjust the temperature from 45°C to 90°C. After waiting for the constant temperature and humidity chamber to stabilize for 15 minutes each time the temperature is adjusted, start using the electrochemical workstation to test the conductivity of the sample.
[0152] (3) After the test, the resistance value Rs is obtained by fitting the Nengquist curve, and the formula The conductivity of the hydrogen-bonded organic framework materials obtained in Example 1, Example 2 and Example 4 was calculated. Wherein, σ is the conductivity, in units of S / cm; Rs is the resistance value, in units of Ω; L is the sample thickness, in units of cm; S is the sample area, in units of cm 2 .
[0153] like Figure 6 As shown, the 1,5-NDS_NH 4 The conductivity of the material reaches 6.6×10 -2 S / cm, BPDS_NH 4 The conductivity of the material reaches 2.1×10 -1 S / cm, MTBS_NH 4 The conductivity of the material reaches 4.6×10 -2 S / cm.
[0154] The results show that the hydrogen-bonded organic framework material of the present invention has excellent thermal stability and electrical conductivity, and its application in proton exchange membrane fuel cells can effectively improve the thermal stability and electrical conductivity of the fuel cell.
[0155] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0156] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A hydrogen-bonded organic framework material, characterized in that: The structural unit of the hydrogen-bonded organic framework material includes a sulfonic acid group and an ammonium ion, and the sulfonic acid group and the ammonium ion are connected by charge-assisted hydrogen bonds to form a three-dimensional hydrogen-bonded network structure; the hydrogen-bonded organic framework material includes at least one of 1,5-NDS_NH4 material, BPDS_NH4 material, and MTBS_NH4 material; the chemical formula of the 1,5-NDS_NH4 material is [(C 10 H8O6S2)(NH4)2]n, the chemical formula of the BPDS_NH4 material is [(C 12 H8O6S2)(NH4)2]n, the chemical formula of the MTBS_NH4 material is [(C 25 H 16 O 12 S4)(NH4)4]n, where n is a positive integer.
2. The hydrogen-bonded organic framework material according to claim 1, characterized in that The 1,5-NDS_NH4 material satisfies at least one of the following: (1) The structural unit of the 1,5-NDS_NH4 material belongs to the monoclinic system, the space group is P21 / c, and the molecular formula is C 10 H 16 N2O6S2, unit cell parameters: α=γ=90°, β=103.4°; (2) The 1,5-NDS_NH4 material is polymerized by multiple repeating units, each repeating unit contains one 1,5-NDS molecule and two ammonium ions, and 1,5-NDS is 1,5-naphthalene disulfonic acid; the sulfonic acid group on the 1,5-NDS molecule and the ammonium ion are repeatedly polymerized to form a three-dimensional hydrogen bond network; (3) The thermal stability temperature of the 1,5-NDS_NH4 material reaches 320°C; (4) The conductivity of the 1,5-NDS_NH4 material at 50-95% RH and 45-90°C is 5.6×10 -6 ~6.6×10 -2 S / cm; where RH is relative humidity.
3. The hydrogen-bonded organic framework material according to claim 1, characterized in that The BPDS_NH4 material satisfies at least one of the following: (a) The structural unit of the BPDS_NH4 material belongs to the monoclinic system, the space group is P21 / c, and the molecular formula is C 12 H 16 N2O6S2, unit cell parameters: α=γ=90°, β=96.7°; (b) The BPDS_NH4 material is polymerized by multiple repeating units, each repeating unit contains one BPDS molecule and two ammonium ions, and BPDS is 4,4'-biphenyldisulfonic acid; the sulfonic acid groups on the BPDS molecules and the ammonium ions are repeatedly polymerized to form a three-dimensional hydrogen bond network; the three-dimensional hydrogen bond network has closed channels and a porosity of 11%; (c) The thermal stability temperature of the BPDS_NH4 material reaches 200°C; (d) The conductivity of the BPDS_NH4 material at 50-95% RH and 45-90°C is 1.7×10 -5 ~2.1×10 -1 S / cm; where RH is relative humidity.
4. The hydrogen-bonded organic framework material according to claim 1, characterized in that The MTBS_NH4 material satisfies at least one of the following: (A) The structural unit of the MTBS_NH4 material belongs to the orthorhombic system, the space group is I4, and the molecular formula is C 25 H 32 N4O 12 S4, unit cell parameters: α=β=γ=90°; (B) The MTBS_NH4 material is polymerized by multiple repeating units, each repeating unit contains 1 MTBS and 4 ammonium ions, and MTBS is tetrakis(4-sulfonatophenyl)methane; the sulfonic acid groups on the MTBS molecules repeatedly polymerize with the ammonium ions to form a three-dimensional hydrogen bond network; (C) The thermal stability temperature of the MTBS_NH4 material reaches 160°C; (D) The conductivity of the MTBS_NH4 material at 50-95% RH and 45-90°C is 2.3×10 -6 ~4.6×10 -2 S / cm; where RH is relative humidity.
5. A method for preparing a hydrogen-bonded organic framework material, characterized in that: The following steps are involved: The sulfonic acid ligand, the solvent and the ammonium source solution are mixed to carry out a polymerization reaction to obtain a mixed solution; The mixed solution is subjected to a crystallization treatment to obtain flaky crystals; The supernatant is removed, and the flaky crystals are naturally dried to obtain a hydrogen-bonded organic framework material.
6. The preparation method according to claim 5, characterized in that: The crystallization treatment method includes at least one of an evaporation crystallization method and a vapor diffusion crystallization method.
7. The preparation method according to claim 6, characterized in that: The vapor diffusion crystallization method includes a poor solvent, and the poor solvent includes at least one of ethyl acetate and acetone.
8. The preparation method according to claim 5, characterized in that: The preparation of the 1,5-NDS_NH4 material includes at least one of the following: (i) the sulfonic acid ligand comprises 1,5-NDS; (ii) the solvent comprises N,N-dimethylformamide; (iii) the ammonium source solution comprises an ammonium chloride solution having a molar concentration of 1 mol / L; (iv) the molar ratio of the 1,5-NDS to the ammonium chloride solution is 1:(2-4); (v) the ratio of the 1,5-NDS to the solvent is 8 to 15 mg / mL; (vi) The crystallization method includes vapor diffusion crystallization.
9. The preparation method according to claim 5, characterized in that: The preparation of the BPDS-NH4 material includes at least one of the following: (I) the sulfonic acid ligand comprises BPDS; (II) the solvent comprises methanol; (III) the ammonium source solution comprises an ammonium chloride solution having a molar concentration of 1 mol / L; (IV) the molar ratio of the BPDS to the ammonium chloride solution is 1:(2-4); (V) The ratio of the BPDS to the solvent is 8-12 mg / mL.
10. The preparation method according to claim 5, characterized in that: The preparation of the MTBS_NH4 material includes at least one of the following: (1) The sulfonic acid ligand comprises MTBS; (2) The solvent includes methanol; (3) the ammonium source solution comprises an ammonium chloride solution having a molar concentration of 1 mol / L; (4) The molar ratio of the MTBS to the ammonium chloride solution is 1:(4-6); (5) The ratio of the MTBS to the solvent is 10 to 12 mg / mL; (6) The crystallization treatment method includes a vapor diffusion crystallization method.
11. A proton exchange membrane, characterized in that: The invention comprises the hydrogen-bonded organic framework material according to any one of claims 1 to 4, or the hydrogen-bonded organic framework material obtained by the preparation method according to any one of claims 5 to 10.
12. A proton exchange membrane fuel cell, characterized in that: Comprising the proton exchange membrane according to claim 11.
Citation Information
Patent Citations
Ionic hydrogen bond organic framework material as well as preparation method and application thereof
CN112552524A
High nuclear water cluster hydrogen bond organic framework material and preparation method thereof
CN113045460A
Ionic hydrogen bond organic framework material as well as preparation method and application thereof
CN113234229A
Organic framework material based on quintuple interpenetrating hydrogen bonds as well as preparation method and application of organic framework material
CN115521474A